Hydrothermal Synthesis and Crystal Structure of 5-Aminoisophthalic acid with 4,4?-Bipyridine Forming Helical Chains via Hydrogen Bonds - ZHANG, XIULING; ZHU, BAOYONG; GUO, FENG (Asian Journal of Chemistry, 2010)
Co-crystallization of 5-aminoisophthalic acid with 4,4'-bipyridine was synthesized and characterized by single-crystal structure determination, IR and elemental analyses. The crystal is orthorhombic, space group Pbca with a = 7.128(2), b = 13.962(5), c = 31.223(11) Å, α = β = γ = 90°, m.f. C18H15N3O4. Mr = 337.33, V = 3107.3(18) Å3, Dc = 1.442 g/cm3, F(000) = 1408, μ = 0.104 cm-1 and Z = 8. The final refinement gave R = 0.0607 and wR = 0.1406 for 2096 reflections with I > 2σ(I). Strong O–H···N hydrogen bonds connect the acid molecules with 4, 4'- bipyridine to form helical chain running along a crystallographic 21 axis in the c direction. The intermolecular π-π staking interactions further assemble the architecture to form a supramolecular framework.